2021
DOI: 10.1038/s41598-021-84475-4
|View full text |Cite
|
Sign up to set email alerts
|

Combination of lymphocyte count and albumin concentration as a new prognostic biomarker for rectal cancer

Abstract: Although numerous studies have highlighted the prognostic values of various inflammation-related markers, clinical significance remains to be elucidated. The prognostic values of inflammation-related biomarkers for rectal cancer were investigated in this study. A total of 448 patients with stage II/III rectal cancer undergoing curative resection were enrolled from the discovery cohort (n = 240) and validation cohort (n = 208). We comprehensively compared the prognostic values of 11 inflammation-related markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Previous studies reported that compared to normal albumin levels, patients with hypoalbuminemia had a lower 5-year survival rate (normal, 78% vs. hypoalbuminemia, 60%) and had lower 5-year recurrence-free rate or 5-years relapse-free survival than normal albumin level (normal, 78.9% vs. hypoalbuminemia, 73.5%). [17][18][19] This study also found a statistically significant association between CRP levels and NAC response. Elevated CRP is a secondary response to tumor necrosis, local tissue damage, and inflammation in malignancy patients.…”
Section: Original Articlesupporting
confidence: 73%
“…Previous studies reported that compared to normal albumin levels, patients with hypoalbuminemia had a lower 5-year survival rate (normal, 78% vs. hypoalbuminemia, 60%) and had lower 5-year recurrence-free rate or 5-years relapse-free survival than normal albumin level (normal, 78.9% vs. hypoalbuminemia, 73.5%). [17][18][19] This study also found a statistically significant association between CRP levels and NAC response. Elevated CRP is a secondary response to tumor necrosis, local tissue damage, and inflammation in malignancy patients.…”
Section: Original Articlesupporting
confidence: 73%
“…We have recently reported the novel prognostic marker “LA”, which means “lymphocyte count × albumin level (g/dL) [ 2 ]. We retrospectively collected data from a total of 448 rectal cancer patients (Stage II and III) from two large centers, and found that low LA (≤5950) was independently associated with both OS and RFS.…”
Section: Albumin-related Markersmentioning
confidence: 99%
“…Previously, we reported that the combination of GPS and NLR could effectively predict the prognosis of CRC patients who underwent curative resection [ 1 ]. In addition, we focused on rectal cancer patients (Stage II and III) and showed that the combination of circulating lymphocyte count and serum albumin concentration could be a useful predictor for prognosis [ 2 ]. However, there are many other inflammation-related biomarkers investigated regarding CRC.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies on the relationship between albumin and the prognosis of solid tumors. (29)(30)(31). The albumin level is also associated with the prognosis of esophageal cancer (32,33).…”
Section: Discussionmentioning
confidence: 99%